2021
DOI: 10.3390/pharmaceutics13111745
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Transport Pathways Associated with Enhanced Brain Delivery of Peptide Drugs by Intranasal Coadministration with Penetratin

Abstract: We previously found that coadministering peptides and proteins with the cell-penetrating peptide L-penetratin intranasally significantly increased transport to the brain and enhanced pharmacological effects. The present study aimed to clarify the mechanisms of nose-to-brain drug delivery enhancement by L-penetratin coadministration. First, we compared the concentrations of Exendin-4 in plasma and brain after intranasal and subcutaneous administration and suggested that coadministration with L-penetratin facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The delivery of MSC-sEVs from the entry point to other distant brain areas after intranasal administration subsequently brought a question: how can this kinetic characteristic be achieved? Researchers have suggested that the perivascular pathway was mostly important to the rapid and widespread distribution of macromolecules in CNS following intranasal delivery [25,26,40], confirmed by the fact that fluorescence-labeled dextrans (3 or 10 kDa), peptide (<10 kDa), or IgG (150 kDa) was rapidly distributed to cerebral PVS. Lochhead et al have shown that the concentration of IgG in PVS of major cerebral arteries at 30 min was higher than that in corresponding brain regions, but consistent with that in the OB and trigeminal nerves [26].…”
Section: Discussionmentioning
confidence: 99%
“…The delivery of MSC-sEVs from the entry point to other distant brain areas after intranasal administration subsequently brought a question: how can this kinetic characteristic be achieved? Researchers have suggested that the perivascular pathway was mostly important to the rapid and widespread distribution of macromolecules in CNS following intranasal delivery [25,26,40], confirmed by the fact that fluorescence-labeled dextrans (3 or 10 kDa), peptide (<10 kDa), or IgG (150 kDa) was rapidly distributed to cerebral PVS. Lochhead et al have shown that the concentration of IgG in PVS of major cerebral arteries at 30 min was higher than that in corresponding brain regions, but consistent with that in the OB and trigeminal nerves [26].…”
Section: Discussionmentioning
confidence: 99%
“…Cell-penetrating peptides are short peptides that can penetrate the cell and/or nuclear membrane to guide any connected peptides, proteins, or other bioactive molecules into cells ( Kamei, 2017 ). Although the precise transmembrane mechanism of cell-penetrating peptides is not fully understood, the effects are likely mediated via signal transduction pathways and endocytosis ( Kamei et al, 2021 ).…”
Section: Methods To Improve Brain-targeted Nasal Mucosal Drug Deliver...mentioning
confidence: 99%
“…53 Such comparison is often used; however, if there are no data of intravenous administration, the activation of the route by delivery tools coadministered intranasally with drugs can be predicted using the alternative way: comparison between the ratio of the brain concentration to the plasma concentration under tool-present conditions and that under tool-free conditions. 54 In this case, when the route of the nose-to-brain delivery works well, the ratio (the brain concentration/the plasma concentration) under delivery tool-present conditions is expected to be larger than that under tool-free conditions. The brain collection was performed along with the blood collection from mice whose data of drug concentrations in the plasma were described in Figure 1.…”
Section: Drug Distribution To the Central Nervous System Under Coadmi...mentioning
confidence: 99%